Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - Sosa-Calvo, J. (2017)
Fungus-farming “attine” ant agriculture consists of five distinct agricultural systems characterized by a remarkable symbiont fidelity in which five phylogenetic groups of ants faithfully cultivate five phylogenetic groups of fungi. Across-system garden switching experiments result in colony decline and death, indicating that attine ant-fungus symbiont fidelity is enforced by poorly understood biological constraints. The most dramatic violation of this pattern of symbiont fidelity occurs in the relict species Apterostigma megacephala, the only lower-attine ant known to cultivate a higher-attine fungus. Apterostigma megacephala is the sole surviving representative of an ancient lineage that diverged from all other Apterostigma fungus-farming ants ~39 million years ago, yet it cultivates Leucoagaricus gongylophorus, a highly domesticated fungal species that originated in the gardens of the recently evolved leaf-cutting ants 8–11 million years ago. Understanding the biology of A. megacephala, therefore, may provide important clues about the biological mechanisms that constrain the otherwise seemingly obligate ant-fungus associations that characterize attine ant agriculture. Here, based on field work in the Floresta Nacional de Carajás in the state of Pará in Brazil, we report the previously unknown biology of A. megacephala, including nest architecture, colony demography, foraging behavior, and the morphologies of the previously undescribed gyne, male, and larva.